Probability of IV Antibiotic Retreatment within Thirty Days is Associated with Duration and Location of IV Antibiotic Treatment for Pulmonary Exacerbation in Cystic Fibrosis - VanDevanter, D. R. (J Cyst Fibros, 2016)
BACKGROUND: There are few objective data to guide management of cystic fibrosis (CF) pulmonary exacerbations. We studied intravenous (IV) antibiotic treatment failure as defined by a need to retreat patients with IV antibiotics within 30 days of completion of a prior IV antibiotic treatment for pulmonary exacerbation. METHODS: The first IV-treated exacerbation on or after Jan 1, 2010 among US CF Foundation Patient Registry patients was studied, combining treatments separated by <7 days into single treatments. IV treatment duration categories were: 1-4, 5-8, 9-12, 13-16, 17-22, and ≥23 days (inclusive). Logistic regressions for IV retreatment in ≤30 days were adjusted with 12 categorical covariates, including age, sex, lung function, prior-year exacerbations, CF complications, CF Care Program, and ever/never treated in hospital. RESULTS: 777 of 13579 patients (5.7%) were retreated within 30 days, with incidence varying by treatment duration: 1-4 days, 8.7%; 5-8 days; 6.6%; 9-12 days, 3.2%; 13-16 days, 4.5%; 17-22 days, 6.2%; ≥23 days, 10.3% and hospitalization: ever, 5.0%; never 8.5%. Adjusted odds ratios (OR) for retreatment (compared to 13-16 days treatment) were: 1-4 days, 1.94 [95%CI 1.49, 2.54] P< .001; 5-8 days, 1.55 [1.18, 2.04] P=.002; 9-12 days, 0.78 [0.58, 1.04] P=.09; 17-22 days, 1.12 [0.88, 1.42] P=.37; ≥23 days, 1.46 [1.12, 1.91] P=.005. Adjusted retreatment OR for never/ever hospitalized was 1.57 [1.29, 1.90] P<.001. Prior-year exacerbation number, oxygen therapy, non-invasive ventilation, and female sex were significantly associated with retreatment. Modeling hazard rate time-dependence showed that treatment duration and location-associated hazard rates attenuated within a few months after treatment. CONCLUSION: After adjustment for covariates known to be associated with increased risk of IV treatment for exacerbation, IV antibiotic treatments of <9 and ≥23 days and those without hospitalization were significant risk factors for IV retreatment within 30 days of completion of an exacerbation treatment.